GPR37 and its neuroprotective mechanisms: bridging osteocalcin signaling and brain function - Bian, Xuepeng; Wang, Yangping; Zhang, Weijie; Ye, Changlin; Li, Jingjing (Frontiers in Cell and Developmental Biology, 2024)
Osteocalcin (OCN) is a hormone secreted by osteoblasts and has attracted widespread attention for its role in regulating brain function. Clinical studies indicate a positive correlation between levels of circulating OCN and cognitive performance. Indeed, lower circulating OCN has been detected in various neurodegenerative diseases (NDs), while OCN supplementation under certain conditions may improve cognitive function. GPR37, a G protein-coupled receptor, has recently been identified as a receptor for OCN. It exhibits distinct expression patterns across various brain regions and cell types, potentially influencing its functional roles within the brain. Research indicates that GPR37 regulates neuronal migration, cell proliferation, differentiation, and myelination. Furthermore, GPR37 has been shown to mitigate inflammation and apoptosis through various mechanisms, exerting neuroprotective effects. However, its regulatory influence on brain function exhibits inconsistency, highlighting a duality in its actions. Therefore, this review thoroughly summarizes the roles and mechanisms of GPR37 in modulating cellular physiological activities and its involvement in immune responses, stress reactions, and neuroprotection. It aims to enhance the understanding of how GPR37 modulates brain function and facilitate the identification of novel therapeutic targets or strategies for related diseases.